2013
DOI: 10.3791/50612
|View full text |Cite
|
Sign up to set email alerts
|

Permeabilization of Adhered Cells Using an Inert Gas Jet

Abstract: Various cell transfection techniques exist and these can be broken down to three broad categories: viral, chemical and mechanical. This protocol describes a mechanical method to temporally permeabilize adherent cells using an inert gas jet that can facilitate the transfer of normally non-permeable macromolecules into cells. We believe this technique works by imparting shear forces on the plasma membrane of adherent cells, resulting in the temporary formation of micropores. Once these pores are created, the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This would explain only minimal leakage of the encapsulated CF from the vesicles with plasma jet treatment. (3) The gas flow itself imparts greater mechanical forces onto the phospholipid membrane of the vesicles [100]. Consequently, greater mechanical forces exerted onto the phospholipid membrane by the higher flow rate plasma jet, enhanced the ingress of RONS.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain only minimal leakage of the encapsulated CF from the vesicles with plasma jet treatment. (3) The gas flow itself imparts greater mechanical forces onto the phospholipid membrane of the vesicles [100]. Consequently, greater mechanical forces exerted onto the phospholipid membrane by the higher flow rate plasma jet, enhanced the ingress of RONS.…”
Section: Discussionmentioning
confidence: 99%
“…Intense pulses of fluid shear can be directed at cells by firing jets of pressurized inert gas toward them 787,788 . Similar to the case of cone-plate viscometers, it was found that excessive shear forces can rip cells from the underlying substrate, but if modulated just below this range, were capable of permeabilizing cell membranes while leaving adherent cells in place.…”
Section: Intracellular Delivery By Permeabilizationmentioning
confidence: 99%
“…With the appropriate optimizations, intracellular delivery of dextrans, plasmids, and other cargo has been demonstrated in common adherent cell lines permeabilized by inert gas jets. 825,826 6.1.12. Fluid Shear: Sonoporation.…”
Section: Mechanical Membrane Disruptionmentioning
confidence: 99%
See 1 more Smart Citation